2013
DOI: 10.3389/fimmu.2013.00226
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary Inhibitors of Histone Deacetylases in Intestinal Immunity and Homeostasis

Abstract: Intestinal epithelial cells (IECs) are integral players in homeostasis of immunity and host defense in the gut and are under influence of the intestinal microbiome. Microbial metabolites and dietary components, including short chain fatty acids (acetate, propionate, and butyrate, SCFAs), have an impact on the physiology of IECs at multiple levels, including the inhibition of deacetylases affecting chromatin remodeling and global changes in transcriptional activity. The number and diversity of butyrate-producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 83 publications
1
74
0
1
Order By: Relevance
“…Beyond the signaling capacity through GPRs, SCFAs and lactate may also modulate histone deacetylase activity and several modulatory effects on macrophages and epithelial cells were also associated with this capacity (Chang et al, 2014;Latham et al, 2012;Schilderink et al, 2013). Furthermore, high concentrations of lactate in extracellular milieu have also effects on modulation of cell metabolism that can contribute to modulation of proinflammatory mediator production (Dietl et al, 2010), we cannot exclude that some of the effects observed here are related to these latter mechanisms.…”
Section: Discussionmentioning
confidence: 60%
“…Beyond the signaling capacity through GPRs, SCFAs and lactate may also modulate histone deacetylase activity and several modulatory effects on macrophages and epithelial cells were also associated with this capacity (Chang et al, 2014;Latham et al, 2012;Schilderink et al, 2013). Furthermore, high concentrations of lactate in extracellular milieu have also effects on modulation of cell metabolism that can contribute to modulation of proinflammatory mediator production (Dietl et al, 2010), we cannot exclude that some of the effects observed here are related to these latter mechanisms.…”
Section: Discussionmentioning
confidence: 60%
“…Inhibitory effect of SCFAs, particularly butyrate, on the expression of IL-8 mRNA was evident, resulting in reduction of IL-8 protein in the supernatant, indicating that the mechanism of IL-8 reduction may be mediated through the inhibition of IL-8 gene expression via inhibition of HDAC (Licciardi et al, 2011;Vinolo et al, 2011;Wu et al, 2012;Schilderink et al, 2013). The different effects of SCFAs in normal versus cancerous cells or inflamed cells may be useful in formulation of the more effective drug that inhibit the inflammation, particularly in IBD with stimulate the growth of normal cells and induce apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 95%
“…Further studies will have to determine whether dietary interventions are able to upregulate Tregs during pregnancy and whether this leads to improved fetal health. 39 …”
Section: Discussionmentioning
confidence: 99%